The role of nurses, midwives, and doulas on breastfeeding: changes during the COVID-19 pandemic - Dhaurali, Shubhecchha; Shrestha, Shikhar (Frontiers in Global Women's Health, 2025)
IntroductionThe COVID-19 pandemic has significantly altered maternal healthcare delivery, including breastfeeding practices. Our study investigated the influence of nurses, midwives, and doulas on breastfeeding education and rates, with a specific focus on changes that transpired during the COVID-19 pandemic.MethodsUsing a cross-sectional design, we performed a secondary data analysis on a stratified systematic sample of forty-six U.S. states and New York City respondents who completed the Pregnancy Risk Assessment Monitoring System (PRAMS) Phase 7 (2012–2015) and Phase 8 (2016–2020) surveys (n = 193,068). Descriptive analyses and adjusted multivariable logistic regression models reporting adjusted odds ratios (aORs) and 95% confidence intervals (95% CIs) were used to assess associations between the provision of breastfeeding guidance to mothers from nurses, doulas, or midwife healthcare professionals; breastfeeding/pumping rates; and the COVID-19 pandemic. Cox-proportional hazard models were used to examine the association between breastfeeding guidance and breastfeeding duration.ResultsOur findings revealed that participants who received breastfeeding guidance from nurses, midwives, or doulas were twice as likely to have engaged in breastfeeding or milk pumping for their infants than participants who did not receive breastfeeding education (aOR = 1.99, 95% CI: 1.89–2.11, p < 0.0001). Additionally, participants who gave birth during the COVID-19 pandemic were notably less likely to receive breastfeeding education from a nurse, midwife, or doula than were those who gave birth before the pandemic (aOR = 0.92, 95% CI: 0.88–0.96, p < 0.0001). We also find that the hazard of stopping breastfeeding was lower among participants who received breastfeeding guidance (HR = 0.94, 95% CI: 0.91–0.97, p < 0.0001). Additionally, the hazard of stopping breastfeeding was lower during COVID-19 (HR = 0.94, 95% CI: 0.91–0.97, p = 0.001)DiscussionOur study underscores the vital role that healthcare professionals play in educating, advocating for, and promoting breastfeeding behaviors. This further highlights the pressing need for sustained efforts to support breastfeeding initiatives and address disparities in maternal and child health, particularly in the context of the challenges presented by the COVID-19 pandemic.